Post-Conflict Reintegration and Special Autonomy in Indonesia: Evaluating the Implementation of Law Number 11 of 2006 and the Role of the Aceh Reintegration Board in Achieving Peace in Aceh - Jamaluddin Jamaluddin; Ghazi Ahmad Tijani (Graha Primera Saintifika, 2025)
Evaluating the implementation of Indonesia’s Law Number 11 of 2006 on the Governance of Aceh and the role of the Aceh Reintegration Board (BRA) in advancing post-conflict reintegration and sustainable peace. Drawing on a qualitative methodology that includes normative legal analysis, document review, and semi-structured interviews with stakeholders, the study examines how legal frameworks and institutional mechanisms translate into practice. Findings reveal that while the BRA has made progress in reintegration through land redistribution and the introduction of digital platforms like SIBRA Online and E-Proposal, its efforts have been hindered by institutional fragmentation, resource constraints, and limited responsiveness to local needs. The shift from individual to shared land ownership models illustrates both policy adaptation and structural limitations. The study contributes to peacebuilding literature by highlighting the interplay between legal mandates and ground-level implementation, underscoring the need for participatory governance and long-term socioeconomic support in post-conflict settings.